The Involvement of Religious Leaders in Conflict Resolution within Tolaki People of Konawe District - Koodoh, Erens Elvianus; Ahimsa Putra, Heddy Shri; Setiadi, Setiadi (Pascasarjana IAIN Pontianak, 2018)
This study aims to identify the various socio-cultural conditions of Tolaki people in Konawe that often engaging in inter-family conflict. The process of identifying the socio-cultural conditions leads to find the correlation between socio-cultural conditions and the types of inter-family conflicts and how they get resolved at the community level. Religious leaders are part of the efforts of solving the conflicts. In addition, this study is also aimed to determine and analyze the types of inter-family conflicts that exist and the processes for conflict resolution among families in the Tolaki in Konawe. The research data is based on two categories of informant; traditional leaders and ordinary informants that are public figures such as religious leaders, government officials within the scope of sub-district, village, and community members both at the level of individuals, families, and communities. The traditional leaders get involved in conflict resolution while public figures have experience on dealing with such conflicts and are sometime involved in a conflict. The work indicates that the conflicts in the Tolaki people take the form of closed and open conflicts. While the sources or the causes of the conflict come from tulura (speech), peowai (actions), and powaihako (behavior). The sources of the conflict then are manifested in the daily life of Tolaki people and become sisala'aineperapua (conflict in marriage), sisala'aine hapo-hapo (conflict by treasure), and conflict in social relations. Social and cultural conditions that often lead to inter-family conflicts are the difference in social strata, economic inequality, and religious differences. Tolaki People then settle their conflict through the expertise and charisma of religious and cultural leaders by the completion of melanggahako, mesokei, peohala, mombopoo'rai, sombalabu, and mosehe.